The New Roget's Thesaurus of The English Language in Dictionary Form - Norman Lewis 1912-2006; Christopher Orlando Sylvester Mawson 1870-1938 (New York G. P. Putnam's sons, 1978)
Christopher Orlando Sylvester Mawson Roget's Thesaurus of the English language in dictionary form
"Based on C.O. Sylvester Mawson's alphabetical arrangement of the famous Roget system of word classification."
Keywords: Languages (3GddZGJs; General -- Synonyms and antonyms; English language; English language -- Dictionaries; Americanisms; Library Edition